2012
DOI: 10.1681/asn.2011050476
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Renal Function on Outcomes of Bariatric Surgery

Abstract: The effect of CKD on the risks of bariatric surgery is not well understood. Using the American College of Surgeons National Surgical Quality Improvement Program Participant Use File, we analyzed 27,736 patients who underwent bariatric surgery from 2006 through 2008. Before surgery, 34 (0.12%) patients were undergoing long-term dialysis. Among those not undergoing dialysis, 20,806 patients (75.0%) had a normal estimated GFR or stage 1 CKD, 5011 (18.07%) had stage 2 CKD, 1734 (6.25%) had stage 3 CKD, 94 (0.34%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 98 publications
3
68
0
1
Order By: Relevance
“…86 In accordance, in a 5-year followup study in 52 obese type 2 diabetic patients who underwent bariatric surgery, diabetic nephropathy resolved in 58%. 87 Turgeon et al 88 reported that, although CKD patients had higher complication rates after bariatric surgery, the absolute incidence of complications remained less than 10%. In our opinion, although there is a somewhat higher risk for complications in CKD patients with morbid obesity and patients at risk for CKD progression, bariatric surgery is an underused treatment option in this population.…”
Section: Treatment Of Obesity In Ckdmentioning
confidence: 99%
“…86 In accordance, in a 5-year followup study in 52 obese type 2 diabetic patients who underwent bariatric surgery, diabetic nephropathy resolved in 58%. 87 Turgeon et al 88 reported that, although CKD patients had higher complication rates after bariatric surgery, the absolute incidence of complications remained less than 10%. In our opinion, although there is a somewhat higher risk for complications in CKD patients with morbid obesity and patients at risk for CKD progression, bariatric surgery is an underused treatment option in this population.…”
Section: Treatment Of Obesity In Ckdmentioning
confidence: 99%
“…Additionally, high rate of post-surgical complications and prolonged hospital stay has been reported in such patients. 2,3 …”
Section: Bariatric Woundsmentioning
confidence: 99%
“…9 Supporting these animal data, human research has confirmed that patients with CKD have a higher rate of wound disruption than individuals with normal GFR. 3 …”
Section: Ckd and Wound Healingmentioning
confidence: 99%
See 2 more Smart Citations